STUDYING FERULA FOETIDA (BUNGE) REGEL POPULATION DISTRIBUTED NEAR TO KHAN-TAU MOUNTAINS (Experimental biology, 2023)
The Ferula foetida species (Bunge) Regel (1877) growing in the natural conditions of Kazakhstan is the most important for traditional and official medicine. This medicinal plant is distributed in five different regions. The F. foetida is classified as an endangered species in some regions because of its illegal harvesting and low seed reproduction. On the territory of the Shu-Ile lowlands, we discovered natural ferula populations near the Khan-Tau mountains, not far from same named village, and in 377 km far from Almaty. Determination of the exact location of plant objects was carried out through the satellite Global Positioning System. A map of location of the Khantau population was developed by the GoogleMyMap programFor the first time, measurement results of quantitative traits of vegetative part of the Khantau population are presented. On average, the height of ferula was 36.9 ± 7.26 cm, the width of basal leave rosette was 107.6 ± 22.45 cm. The total number of rosette leaves was 7.0 ± 1.71 cm, and their width and length were 63.4 ±11.27 cm and 61.1 ±9.86 cm, respectively. The length of ferula root system was 204.2 ± 55.82 cm in average, while the length of turnip rhizome was 33.4 ± 6.58 cm.The resin is released from this thickened rhizome, and common using for food. The diameter of the turnip-shaped root was on average 19.3 ± 6.83 cm. The fresh weight of model root specimens was varying from 1.61 to 7.75 kg. The average yield of the raw material from Khantau population was 469 kg/ha. Despite the small size of studied population, further studies of all 10 districts seem promising to assess the total reserves of medicinal ferula in the Zhambyl region, which, like the Turkestan populations, are subject to illegal procurement and export outside our Republic.
Keywords: Ferula L; endangered species; medicine plant; raw material; rhizome